Density Gradient Centrifugation and Electron Microscopic Characterization of Subcellular Fractions from Human Blood Platelets - Siegel, A; Burri, P. H; Weibel, E. R; Bettex-Galland, M; Lüscher, E. F (Thrombosis and Haemostasis, 1971)
Homogenized human blood platelets have been fractionated by centrifugation in Ficoll and sucrose density gradients. The different fractions were examined by electron microscopy.Although Ficoll allows for the separation of very distinct zones, its ability to form complexes with cellular components made sucrose the preferable gradient. Sucrose, in spite of its unfavorable osmotic effect, allows for an acceptable fractionation of platelet components.